Evaluation of therapeutic adherence in childhood asthma and its relationship with parenting practices - Graterol Velásquez, Andreina Coromoto; López Andrade, José Manuel; Álvarez García, Yazmin Isolda; Páez Barcasnegras, Yimara Lisset; Quiroz Gómez, Sergio (Horizonte Sanitario, 2025)
Objective: To determine the level of adherence to inhaler use and its relationship with inhalation technique and asthma control in patients aged 6-11 years treated at the outpatient clinic of Hospital General de Zona No. 46 (HGZ-46) IMSS Tabasco, during the period March 2024 to February 2025. Material and method: An observational, analytical, cross-sectional study was conducted in pediatric patients diagnosed with asthma who used inhaled corticosteroids, n=100. The TAI-10 and 12 items were applied, adjusted to a validated list of 10 critical steps in inhalation technique and the Childhood Asthma Control Test (C-ACT). Caregivers answered a KAP-BMQ questionnaire. Descriptive statistics and multivariate logistic regression were estimated. Results: Overall, 68% achieved clinical control (C-ACT>19). Mean TAI was 44±6; good, intermediate and poor adherence were 27%, 31% and 42%, respectively. In adjusted models, good (aOR 9.99; 95%CI 2.64–37.81; p=0.001) and intermediate adherence (aOR 7.71; 95%CI 1.92–30.92; p=0.004), and ≤1 critical error (aOR 3.49; 95%CI 1.12–10.90; p=0.032) were associated with higher odds of control. Conclusions: Adherence and technical competence in inhaler use are modifiable determinants of asthma control in children. Multicomponent interventions focused on parental education and inhaler retraining are required to improve respiratory outcomes in children. Keyword: Adherence; Inhaler; Asthma; Pediatric; Education.